Longitudinal Measurements of Resting Energy Expenditure by Indirect Calorimetry in Healthy Term Infants during the First 2 Months of Life - Verma, Sourabh; Bailey, Sean M.; Mally, Pradeep V.; Howell, Heather B. (American Journal of Perinatology, 2019)
Objective To determine longitudinal measurements of resting energy expenditure (REE) by indirect calorimetry (IC) in healthy term infants during the first 2 months of life.Study Design An outpatient prospective pilot study was performed in healthy term infants to estimate REE by measuring expired gas fractions of oxygen (O2) and carbon dioxide (CO2) with IC in a respiratory and metabolic steady state.Results A total of 30 measurements were performed. Fourteen subjects completed measurements at both 1 and 2 months of life, and two subjects had only measurements made at 1 month of life. Mean REE values were 64.1 ± 12.7 and 58.4 ± 14.3 kcal/kg/d at 1 and 2 months of age, respectively. Mean O2 consumption and CO2 production measurements were 9.3 ± 2.0 and 7.7 ± 1.2 mL/kg/min and 8.1 ± 2.2 and 6.4 ± 1.1 mL/kg/min at 1 and 2 months of age, respectively.Conclusion This pilot study demonstrates longitudinal measurements of REE by IC in healthy term infants during the first 2 months of life. We also demonstrate that, overall, there is consistency in REE values in this population, with a likely decrease in individual longitudinal measurements over the first 2 months of life.
Keywords: resting energy expenditure; indirect calorimetry; healthy term infants; nutrition